The Analysis Of The Student's Accuracy Communication Intraction And Fluency In Their Speaking Ability At The Tenth Grade Of Ma Nawawi Djamil Muhammadiyah Duri - Asrinal Hasibuan; Mohd. Rafi Riyawi; Zulfia Siska Wati; Deny Silvia (DIMAR: Jurnal Pendidikan Islam, 2019)
The research aimed to know the students’ speaking ability at the tenth Grade of MA Nawawi Djamil Muhammadiyah Duri, by using accuracy, communication, interaction, and fluency to assess their speaking ability. Speaking is a productive language skill. It means that speaking is a person’s skills to produce sounds that exists at the meaning and be understood by other people, so that able to create of good communication. The research population was tenth grade students of MA Nawawi Djamil Muhammadiyah Duri in the academic year 2017/2018. The population of the research is 10 students. The sample technique is population sampling. To perform the data, researcher used descriptive quantitative approach. Therefore, it related with statistic, so that researcher uses SPSS V. 17 to analyze the data. To make the reader easy to understanding this research, the data will be presented in tables and chart form. In order to investigate students’ accuracy, communication, interaction, and fluency the researcher using oral test it was speaking test. After doing the research of students’ accuracy, communication, interaction and fluency in their speaking ability, researcher obtained the result of total mean score is 61.00 “Passed” category.